Endocrinological approach to adolescents with gender dysphoria: experience of a pediatric endocrinology department in a tertiary center in Turkey - ERDOĞDU, AYŞE BURCU (My University, 2023)
Objective: A significant rise in the number of trans adolescents seeking medical interventions has been reported in recent years. The aim of this study was to report the clinical features, treatment, and follow-up of adolescents with gender dysphoria (GD) with our increased experience. Methods: Twenty-six male-to-female (MTF) and twenty-seven female-to-male (FTM) adolescents who were referred to the GD-outpatient clinic between 2016 and 2022 were reviewed. The clinical and laboratory findings of thirty transgender adolescents (15 FTM /15 MTF) who received medical intervention were evaluated retrospectively. Results: Most individuals (60.4%) were admitted between 2020 and 2022, and the remaining (39.6%) were admitted between 2016 and 2019. At the time of referral, median age was 16.3 years [interquartile range (IQR) 1.53; range 13.2-19.4] in 26 MTF, and 16.4 years (IQR 1.74; range 11.7-21.6) in 27 FTM adolescents. The median age at pubertal blockage with gonadotropin-releasing hormone analog and androgen receptor blocker was 16.4 years (IQR 1.4; range 11.7-17.8) in 22 adolescents (9 MTF, 13 FTM), and 17.4 years (IQR 1.4; range 15.5-19.4) in 6 MTF individuals, respectively. Cross-sex hormone therapy was commenced in 21 adolescents (12 MTF, 9 FTM) at the median age of 17.7 years (IQR 0.61; range 16-19.5). Fifteen individuals (8 MTF, 7 FTM) have been transferred to the adult endocrinology department in transition clinics. Conclusion: All treatments were generally well tolerated and effective, including bicalutamide, and no significant side effects were observed. Transition clinics played an important role in the better management of gender reassignment processes.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Pediatrics, Perinatology and Child Health; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; bicalutamide; cross-sex hormone; gender reassignment; gonadotropin-releasing hormone treatment; multidisciplinary follow-up; Transgender; transition; Transgender; gender reassignment; gonadotropin-releasing hormone treatment; bicalutamide; cross-sex hormone; transition; multidisciplinary follow-up